Archaeological Survey of a Power Line in Macon County, N.C., Along the Little Tennessee River Valley from Otto To Franklin (Er 85-7786) - Ayers, Harvard G. (the Digital Archaeological Record)
This resource is a citation record only, the Center for Digital Antiquity does not have a copy of this document. The information in this record has been migrated into tDAR from the National Archaeological Database Reports Module (NADB-R) and updated. Most NADB-R records consist of a document citation and other metadata but do not have the documents themselves uploaded. If you have a digital copy of the document and would like to have it curated in tDAR, please contact us at comments@tdar.org.